Pathways to inclusive higher education: learnings from India’s National Education Policy 2020 - Shravan B Raj (Nordic Journal of Studies in Educational Policy)
The National Education Policy (NEP) 2020 of India has been widely recognized as a significant and transformative reform endeavour, with the objective of reshaping the educational framework of the country. The aims to establish an education system deeply rooted in Indian Ethos, with the objective of transforming India, also known as Bharat, into a sustainable, equitable, and vibrant knowledge society. The policy seeks to achieve this by ensuring access to high-quality education for all individuals, thereby positioning India as a global knowledge superpower. This paper provides an understanding about the provisions and prospective effect of the NEP 2020 on historically marginalized students in the realm of higher education. In an era marked by a global movement that brings attention to the marginalization and underrepresentation experienced by some groups inside educational institutions, this study poses a crucial question: Can the Indian higher education system effectively cultivate inclusivity? This study compares the higher education initiatives of Nordic region with India in the framework of equity and inclusive education. This article concludes with the ideas for promoting inclusivity, particularly by addressing the educational challenges faced by underprivileged students to enhance the Education system both in India and in Nordic regions.